The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.787710
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Systems Study on Complexity, Accuracy, and Fluency in English Writing Development by Chinese University Students

Abstract: This study investigated the development of lexical complexity, sentence complexity, accuracy, and fluency in the English writing of 22 Chinese university students from the perspective of Complex Dynamic Systems Theory (CDST). Compositions were assigned 30 times over the course of one academic year through Pigaiwang, an online platform that automatically evaluates writing. A modified retrodictive modeling approach was adopted. Specifically, a longitudinal cluster analysis was used to examine emergent prototypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…The innumerable individual and extraneous variables that impact second language acquisition make this development a dynamic one. A few of such variables include affect, motivation, environmental factors (Khomeijani et al, 2020;Zhang et al, 2022), age of onset (Pfenninger, 2022), first language fluency, individual learner investment, amount of available free time, and competition among learners (Kliesch & Pfenninger, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The innumerable individual and extraneous variables that impact second language acquisition make this development a dynamic one. A few of such variables include affect, motivation, environmental factors (Khomeijani et al, 2020;Zhang et al, 2022), age of onset (Pfenninger, 2022), first language fluency, individual learner investment, amount of available free time, and competition among learners (Kliesch & Pfenninger, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While the value of the contributions and findings of group studies even with few data points is undeniable, such studies are unable to keep track of the unique and flexible developmental trends of each learner. Some of the numerous cognitive and environmental factors that impact the dynamic development of a second language include motivation, anxiety, memory capacity, age, aptitude, intelligence, available learning time, available knowledge, level of education, maturity, and the amount of exposure to the new language (de Bot et al, 2007;Kliesch & Pfenninger, 2021;Zhang et al, 2022). For example, the study conducted by Piniel and Csizér (2015) indicated that learners with higher degrees of motivation and lower degrees of anxiety had more variable developmental patterns in comparison with others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, particularly within the realm of higher education, there exists a critical need for a paradigm shift that addresses the persistent challenges faced by university students in their English communication skills (Hu et al, 2023), notably in writing and speaking (Lin & Liu, 2022;Yang, 2020). Despite the substantial emphasis on English language instruction, students often encounter deficiencies in complexity, accuracy and fluency (CAF) in their expressive abilities (Wang & Han, 2021;Zhang et al, 2022), raising concerns amplified by the recognition that effective English communication skills are integral not only to academic success but also to participating meaningfully in a globalized society and workforce (Hu et al, 2022). Amidst these challenges, the Production-Oriented Approach (POA) has recently emerged in China's academia as a promising pedagogical strategy designed to address the shortcomings of traditional foreign language (L2) instruction characterized by an over-emphasis on linguistic forms (Zhang, 2020b).…”
Section: Introductionmentioning
confidence: 99%